2015
DOI: 10.1007/s00236-015-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

CCS: It’s not fair!

Abstract: In the process algebra community it is sometimes suggested that, on some level of abstraction, any distributed system can be modelled in standard process-algebraic specification formalisms like CCS. This sentiment is strengthened by results testifying that CCS, like many similar formalisms, is Turing powerful and provides a mechanism for interaction. This paper counters that sentiment by presenting a simple fair scheduler-one that in suitable variations occurs in many distributed systems-of which no implementa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
(99 reference statements)
1
20
0
Order By: Relevance
“…The above reasoning merely shows that the given implementation of Peterson's mutual exclusion protocol in CCS requires fairness to be correct. In [20] we show that the same holds for any implementation of any mutual exclusion protocol in CCS, and the same argument applies to a wider class of process algebras. Peterson expressed his protocol in pseudocode without resorting to a fairness assumption.…”
Section: Why the Ccs Rendering Of Peterson's Algorithm Is Unsatisfactorysupporting
confidence: 55%
See 2 more Smart Citations
“…The above reasoning merely shows that the given implementation of Peterson's mutual exclusion protocol in CCS requires fairness to be correct. In [20] we show that the same holds for any implementation of any mutual exclusion protocol in CCS, and the same argument applies to a wider class of process algebras. Peterson expressed his protocol in pseudocode without resorting to a fairness assumption.…”
Section: Why the Ccs Rendering Of Peterson's Algorithm Is Unsatisfactorysupporting
confidence: 55%
“…In [20] it is shown that Peterson's mutual exclusion protocol [31] cannot be expressed in CCS without assuming fairness. In this section we briefly recapitulate the protocol itself and present an optimal rendering in CCS.…”
Section: Peterson's Mutual Exclusion Protocol-part Imentioning
confidence: 99%
See 1 more Smart Citation
“…In [18,27] we argue that a justness assumption is essential for the validity of any mutual exclusion protocol. It appears that in the correctness arguments of famous mutual exclusion protocols appearing in the literature [35,49] the relevant justness assumption is taken for granted, without explicit acknowledgement that the correctness of the protocol rests on the validity of this assumption.…”
Section: Justnessmentioning
confidence: 99%
“…In CCS, the only non-blocking action is τ . However, for certain applications it makes sense to declare some other actions to be non-blocking [27]; this constitutes a promise that we will never put the system in an environment that can block these actions. In [28] we use a process algebra with broadcast communication: a broadcast counts as a non-blocking action, because it will happen regardless whether anyone receives it.…”
Section: Reactive Systemsmentioning
confidence: 99%